Pemenuhan Aksesibilitas Pelayanan Publik Bagi Penyandang Disabilitas Di Kecamatan Baguala Kota Ambon - Tuakora, Syeren Claudya; Rolobessy, Mike Jurnida; Rukoyah, Rukoyah (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2024)
Persons with disabilities are a vulnerable group of people who need special attention from the government, not only in big cities, but also evenly distributed in regions and villages. Accessibility and public service facilities that have been built and provided must be ensured to be suitable and easy to use according to the needs of the community, including people with disabilities. Accessibility is actually not only the responsibility of individuals and the government, but also every level of society with a supportive environment. The public is also required to have awareness of knowledge of the problems of people with disabilities in order to eliminate societal stigma which often creates discrimination against people with disabilities.